2020
DOI: 10.1186/s12913-020-05213-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hospital language on the rate of in-hospital harm. A retrospective cohort study of home care recipients in Ontario, Canada

Abstract: Background: Patients who live in minority language situations are generally more likely to experience poor health outcomes, including harmful events. The delivery of healthcare services in a language-concordant environment has been shown to mitigate the risk of poor health outcomes related to chronic disease management in primary care. However, data assessing the impact of language-concordance on the risk of in-hospital harm are lacking. We conducted a population-based study to determine whether admission to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…Language discordance can negatively impact access to healthcare services, quality of healthcare services, and patient outcomes [14,15]. Previous studies have shown that residents who live in minority language situations face barriers when accessing healthcare services [16,17], have longer emergency department visits and hospitals stays [18,19], have higher rates of hospital admissions and re-admissions [20][21][22], and experience more harmful events in hospitals [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Language discordance can negatively impact access to healthcare services, quality of healthcare services, and patient outcomes [14,15]. Previous studies have shown that residents who live in minority language situations face barriers when accessing healthcare services [16,17], have longer emergency department visits and hospitals stays [18,19], have higher rates of hospital admissions and re-admissions [20][21][22], and experience more harmful events in hospitals [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of 2 studies conducted in the acute care setting, with 1 showing that Francophones residing in Ontario were less likely to experience harm when they were treated in hospitals that were required by law to provide services French. 20,21 We sought to compare the risk of adverse, hospital-related outcomes among frail patients living in Ontario, Canada, after stratifying by patient language and patient-physician language concordance or discordance. We hypothesized that patients receiving language-concordant care would have better outcomes than those receiving language-discordant care.…”
mentioning
confidence: 99%
“…3 Residents who live in minority language situations face barriers when accessing health care services; 4 in some situations, the care provided to these patients has been shown to be inferior with respect to both quality and safety. For instance, patients living in minority language situations are subject to higher rates of harmful events, [5][6][7][8][9] return emergency department (ED) visits, 10,11 and re-admissions to hospital. [11][12][13][14] They also experience longer stays in hospitals, [15][16][17] even after adjusting for differences in sociodemographic characteristics and health status.…”
mentioning
confidence: 99%